Influence of Lithology on Reactive Melt Flow Channelization. (16th August 2020) - Pec, M.; Holtzman, B. K.; Zimmerman, M. E.; Kohlstedt, D. L.
Abstract: To investigate channelization during migration of a reactive melt, we performed a series of Darcy‐type experiments in which an alkali basalt infiltrated partially molten harzburgites and lherzolites at a confining pressure of 300 MPa, temperatures of 1200°C and 1250°C, and pore pressure gradients of ~2 to 60 MPa/mm. We compare our results to those from previously published experiments performed on wehrlites. In all experiments, irrespective of the exact mineralogy, a planar reaction layer composed of olivine + melt developed in which all of the pyroxene was consumed. Under specific conditions controlled primarily by the melt flow velocity, finger‐like channels composed of olivine + melt also developed. In wehrlites, these reaction infiltration instabilities formed at 1200°C and 1250°C at pressure gradients >25 and >5 MPa/mm, respectively. In harzburgites, channelization occurred only at 1250°C at a pressure gradient of 35 MPa/mm. In lherzolites, a planar melt‐filled vein developed at 1250°C; no finger‐like channels formed under a pressure gradient of ~25 MPa/mm. Both the finger‐like channels and the planar vein led to very efficient extraction of melt from the reservoir. Channelization established large compositional variations over short distances in the crystalized phases as well as in the local melt and greatly enhanced the abundance of the reaction product, olivine, similar to dunite channels in the Earth. The range of chemical‐mechanical responses displayed by this array of compositions provides a set of targets for reactive transport and mechanical modeling studies. Key Points: Reaction infiltration instability develops in experiments on wehrlites and harzburgites Channelization establishes large compositional variations over short distances in the crystalized phases as well as in local melt Channelization greatly increases the modal abundance of olivine in the partially molten rock